The Effect of Work Discipline and Work Motivation on Production Employee Work Productivity at PT. Smartfen Telecom Tbk BSD South Tangerang - Pusporini Palupi Jamaludin; Ratih Purwasih; Paringsih (Indonesian Journal of Economic & Management Sciences, 2023)
This study examines the effect of work discipline and motivation on the productivity of production workers at PT Smartfren Telecom Tbk BSD-Tangerang Selatan. Total population of 90 employees of PT Smartfren Telecom participated in this study; The sampling technique used is saturated sampling technique, and the data collection technique is a questionnaire sampling technique. The results of the linear regression analysis show that Y = 4.864 + 0.170X1 + 0.702X2 is correct. Conversely, the correlation elasticity coefficient of 0.591 indicates that the variables of work discipline (X1) and work motivation (X2) have a current threshold relationship with employee productivity (Y)